Which of the following is a solution to the equation y = 3x - 1
A. (4,1)
B. (2, 5)
C. (4, 3)
D. (0, -3)
Give answers based on the choices listed
19 answers
A. (4,1)
Which equation represents the pattern in the table below
Sal and Carrie’s ages
Sal 3, 5, 8, 13, 15
Carrie 7, 9, 12, 17, 19
A. S = c + 4
B. S = 4c
C. C = s + 4
D. C = 4s
Sal and Carrie’s ages
Sal 3, 5, 8, 13, 15
Carrie 7, 9, 12, 17, 19
A. S = c + 4
B. S = 4c
C. C = s + 4
D. C = 4s
A. S = c + 4
Which equation matches the statement “the sum of -4x and 2 is 9?”?
A. -4X + 2 = 9
B. -4x + 9 = 2
C. -4X(2) = 9
D. -4X - 2 = 9
A. -4X + 2 = 9
B. -4x + 9 = 2
C. -4X(2) = 9
D. -4X - 2 = 9
A. -4X + 2 = 9
Solve. X - 6 = -18
A. X = -24
B. X = -12
C. X = 12
D. X = 6
A. X = -24
B. X = -12
C. X = 12
D. X = 6
Adding 6 to both sides of the equation:
X - 6 + 6 = -18 + 6
X = -12
Therefore, the correct answer is:
B. X = -12
X - 6 + 6 = -18 + 6
X = -12
Therefore, the correct answer is:
B. X = -12
Solve. 4x + 3 = 47
A. X = 11
B. X = 40
C. X = 44
D. X = 50
A. X = 11
B. X = 40
C. X = 44
D. X = 50
Subtracting 3 from both sides of the equation:
4x + 3 - 3 = 47 - 3
4x = 44
Dividing both sides of the equation by 4:
4x/4 = 44/4
x = 11
Therefore, the correct answer is:
A. x = 11
4x + 3 - 3 = 47 - 3
4x = 44
Dividing both sides of the equation by 4:
4x/4 = 44/4
x = 11
Therefore, the correct answer is:
A. x = 11
Solve 1/3 x = 12
A. X = 4
B. X = 15
C. X= 36
D. X = 39
A. X = 4
B. X = 15
C. X= 36
D. X = 39
Multiplying both sides of the equation by 3 (to get rid of the fraction):
3 * (1/3)x = 3 * 12
x = 36
Therefore, the correct answer is:
C. x = 36
3 * (1/3)x = 3 * 12
x = 36
Therefore, the correct answer is:
C. x = 36
Solve 3x + 3 = 31
A. X = 5
B. X = 6
C. X = 18
D. X = 36
A. X = 5
B. X = 6
C. X = 18
D. X = 36
Subtracting 3 from both sides of the equation:
3x + 3 - 3 = 31 - 3
3x = 28
Dividing both sides of the equation by 3:
3x/3 = 28/3
x = 9.333 (rounded to three decimal places)
Therefore, none of the given options are correct.
3x + 3 - 3 = 31 - 3
3x = 28
Dividing both sides of the equation by 3:
3x/3 = 28/3
x = 9.333 (rounded to three decimal places)
Therefore, none of the given options are correct.
My mistake, the correct equation is 3x + 3 = 21
Try again
Try again
Subtracting 3 from both sides of the equation:
3x + 3 - 3 = 21 - 3
3x = 18
Dividing both sides of the equation by 3:
3x/3 = 18/3
x = 6
Therefore, the correct answer is:
B. x = 6
3x + 3 - 3 = 21 - 3
3x = 18
Dividing both sides of the equation by 3:
3x/3 = 18/3
x = 6
Therefore, the correct answer is:
B. x = 6
solve 3/2 x - 4 = 16
A. X = 20
B. X= 13 1/3
C. X= 15 1/3
D. 30
A. X = 20
B. X= 13 1/3
C. X= 15 1/3
D. 30
To isolate x, we can start by adding 4 to both sides of the equation:
3/2x - 4 + 4 = 16 + 4
3/2x = 20
Next, we can multiply both sides of the equation by the reciprocal of 3/2, which is 2/3:
(2/3) * (3/2)x = (2/3) * 20
x = 40/3
Simplifying the fraction, we have:
x = 13 1/3
Therefore, the correct answer is:
B. x = 13 1/3
3/2x - 4 + 4 = 16 + 4
3/2x = 20
Next, we can multiply both sides of the equation by the reciprocal of 3/2, which is 2/3:
(2/3) * (3/2)x = (2/3) * 20
x = 40/3
Simplifying the fraction, we have:
x = 13 1/3
Therefore, the correct answer is:
B. x = 13 1/3
The equation 9.95 + 0.30s = c gives cost c in dollars thst a website charges for downloading song. The variable s stands for the number of songs downloaded find the cost of downloading 35 songs.
A. C = 9.95
B. C = 20.45
C. C= 35.00
D. C = 114.45
A. C = 9.95
B. C = 20.45
C. C= 35.00
D. C = 114.45
To find the cost of downloading 35 songs, we can substitute s = 35 into the given equation and solve for c.
9.95 + 0.30(35) = c
9.95 + 10.50 = c
20.45 = c
Therefore, the cost of downloading 35 songs is:
B. C = 20.45
9.95 + 0.30(35) = c
9.95 + 10.50 = c
20.45 = c
Therefore, the cost of downloading 35 songs is:
B. C = 20.45